inlF Enhances Listeria monocytogenes Early-Stage Infection by Inhibiting the Inflammatory Response - Ling, Zhiting; Zhao, Dan; Xie, Xinyu; Yao, Hao; Wang, Yuting; Kong, Suwei; Chen, Xiang; Pan, Zhiming; Jiao, Xin’an; Yin, Yuelan (Frontiers in Cellular and Infection Microbiology, 2022)
The internalin family proteins, which carry the leucine repeat region structural motif, play diverse roles in Listeria monocytogenes (Lm) infection and pathogenesis. Although Internalin F, encoded by inlF, was identified more than 20 years ago, its role in the Lm anti-inflammatory response remains unknown. Lm serotype 4b isolates are associated with the majority of listeriosis outbreaks, but the function of InlF in these strains is not fully understood. In this study, we aimed to elucidate the role of inlF in modulating the inflammatory response and pathogenesis of the 4b strain Lm NTSN. Strikingly, although inlF was highly expressed at the transcriptional level during infection of five non-phagocytic cell types, it was not involved in adherence or invasion. Conversely, inlF did contributed to Lm adhesion and invasion of macrophages, and dramatically suppressed the expression of pro-inflammatory cytokines interleukin (IL)-1β and tumor necrosis factor (TNF-α). Consistent with the in vitro results, during Lm infection mice, inlF significantly inhibited the expression of IL-1β and IL-6 in the spleen, as well as IL-1β, IL-6, and TNF-α in the liver. More importantly, inlF contributed to Lm colonization in the spleen, liver, and ileum during the early stage of mouse infection via intragastric administration, inducing severe inflammatory injury and histopathologic changes in the late stage. To our knowledge, this is the first report to demonstrate that inlF mediates the inhibition of the pro-inflammatory response and contributes to the colonization and survival of Lm during the early stage of infection in mice. Our research partly explains the high pathogenicity of serovar 4b strains and will lead to new insights into the pathogenesis and immune evasion of Lm.